Design a Model for the Association among Transition Shock, Empathy, Resilience, and Coping Strategies with Professional Quality of Life - Younes, Hanan Sayed; Abdallah, Samah Mohamed; Ghallab, Soad Ahmed (International Journal of Membrane Science and Technology, 2023)
Background: Many newly graduated nurses left nursing careers within the first year of practice. So, the high turnover rate of new nurses exacerbates the nursing shortage and causes a serious waste of nursing education resources and the financial costs of hospitals. Aims: To design a model for the association among transition shock, empathy, resilience, and coping strategies with professional quality of life among newly graduated nurses. Design: a predictive correlational study design was used. Setting: The study was conducted at Assiut University Hospitals, (General Medical Surgical, Pediatric, Obstetrics and Gynecology, Urology, Neurology and Psychiatry, EL- Rajhi-Liver, and Cardiology hospitals). Subject and Method: A convenient sample was used with a total numbers of 256 newly graduated nurses (within the first year of employment) working at the mentioned hospitals. The data collected through self-administered questionnaires includes socio-demographic data, a transition shock scale, an empathy scale, a resilience scale, a coping strategies questionnaire, and a professional quality of life scale. Results: There was a statistically significant positive correlation between empathy, resilience, coping strategies, and professional quality of life, except between transition shock and professional quality of life. Conclusion: More than one third (40.6%) of the studied participants suffer from moderate levels of transition shock.